Pelatihan Cara Penanaman TOGA untuk Meningkatkan Kemampuan dan Keterampilan Warga Desa Ngenep - Mas’ula, Siti; Ahdhianto, Erif; Thohir, M. Anas; Iruntyasari, Nevy (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Ngenep Village is one of the villages in Karangploso District, Malang Regency which has abundant potential in the fields of plantations and agriculture. Most of the land in this village area is classified as fertile. Seeing this potential, we as implementers of the Malang State University Community Service Activities try to help develop the potential of Ngenep Village through community empowerment activities in the form of training on how to plant Family Medicinal Plants (TOGA). The service activity aims to improve the abilities and skills of the villagers of Ngenep in managing the TOGA garden. The method used in this activity is the method of lecture, demonstration, discussion and question and answer. The implementation of this activity begins with the lecture method, namely the delivery of TOGA material, then participants and presenters conduct discussions and ask questions about the material. After that, it was continued with demonstration activities on how to plant TOGA which was carried out on plantation land. After the implementation of this activity, it is hoped that the residents of Ngenep Village can gain a lot of knowledge about TOGA, so that they can develop a TOGA garden using appropriate management methods.